Independence of Internal Audit Unit Influence the Internal Audit Capability of Malaysian Public Sector Organizations - Ain Zakiah Mohd Yusof, Nur; Haron, Hasnah; Ismail, Ishak; Hock Chye, Ong (KnE Social Sciences, 2019)
Measuring capability level of a service provider is ambiguous, so does an internal audit unit in the public sector. Prominently, there is very scarce research conducted on this issue. In this study, the Internal Audit Capability Model (IACM) is used to measure the capability while the independence of the internal audit is studied as one of the factors influencing it. Questionnaires were sent to head of internal auditors which list obtained from National Audit Department. Total of 70 responses was received and analyzed for descriptive statistics and relationship testing using SPSS and SmartPLS. It was found that 47 organizations were only at capability level 1 Initial while remaining 13 organizations were at least scored capability Level 2 Infrastructure. This shows that the Malaysian public sector must strengthen its internal audit unit, especially in People Management, to develop higher capability level. It was also found that independence of the internal audit unit has a positive and significant influence on the overall internal audit capability level. Lack of independence results in lack of quality internal audit unit thus gives an impact on the capability level. IACM used in this study could provide the organization with a road map to enhance its capability.